Brexit outside of UK politics: the case of Czech Eurosceptics. Issue 5 (20th October 2018) - Kaniok, Petr; Hloušek, Vít
ABSTRACT: How do soft and hard Eurosceptics differ from each other? This question has become more salient in recent years, as party-based Euroscepticism has been affecting daily mainstream European politics. This article explores this question through an examination of the impact of Brexit outside the United Kingdom. Using the Czech Republic, a country with a strong tradition of party-based Euroscepticism, we analyze representatives of both categories in the context of pro-EU parties. Using official party reactions to Brexit, we argue that the reactions of both camps substantially vary. While soft Eurosceptics consider Brexit to be an opportunity to reform the EU, hard Eurosceptics see Brexit as a call to destroy the EU. Moreover, the position of soft Eurosceptics is closer to the stance of pro-EU parties than to that of hard Eurosceptics. Our research thus contributes to a greater understanding of party-based Euroscepticism and to forming a clearer conceptualization of it.